Sperm Kinematics and Morphology of Bali Bull (Bos javanicus) after Freezing and Thawing Treated with Green Tea Extract in Extender - Prastiya, R. A.; Debora, A. E.; Wijayanti, A.; Agustono, B.; Saputro, A. L.; Amalia, A.; Sasi, S. M. (Tropical Animal Science Journal, 2023)
Green Tea Extract, or GTE, is a powerful antioxidant that can be added to the extender to maintain the quality of Bali bull semen before and after freezing. This study aimed to evaluate the impact of the GTE addition in the extender on the sperm kinematic and sperm morphology from frozen semen of Bali bull. Five Bali bulls from the NAIC, were used as semen sources. In this study, there were four different treatments: a control (Tris-egg yolk without GTE), a GTE0.05 (100 mL tris egg yolk with 0.05 mg of GTE), a GTE0.10 (100 mL tris egg yolk with 0.10 mg of GTE), and a GTE0.15 (100 mL tris egg yolk with 0.15 mg of GTE). A sperm analyzer (CASA) was used to observe the sperm kinematics and morphology. Compared to the control group, adding different concentrations of GTE to the semen extender did not affect the sperm’s morphology. Before freezing, adding GTE0.05 increases total and progressive motility as well as VAP, VCL, and VSL after thawing. GTE0.15 increases STR and ALH. The conclusion is that GTE additions at doses of 0.05 mg/100 mL and 0.15 mg/100 mL can increase sperm kinematics parameters, but sperm morphology is not affected by the GTE.